2008
DOI: 10.1111/j.1742-6723.2008.01066.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of high‐dose midazolam for severe behavioural disturbance in an emergency department with suspected psychostimulant‐affected patients

Abstract: High-dose midazolam protocols cannot be supported as universally safe. High-dose protocols for severe behavioural disturbance are not more effective, with failures occurring even after repeated dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…One study comparing IM ziprasidone, droperidol and midazolam reported respiratory depression in 15% of patients[3], similar to our study. Another study of high dose midazolam in acutely agitated ED patients, where two thirds received it via the IM route, reported adverse events in eight of 61 patients (13%)[16]. The drug was not known for each patient in our study and may differ between those receiving droperidol, midazolam or both.…”
Section: Discussionmentioning
confidence: 80%
“…One study comparing IM ziprasidone, droperidol and midazolam reported respiratory depression in 15% of patients[3], similar to our study. Another study of high dose midazolam in acutely agitated ED patients, where two thirds received it via the IM route, reported adverse events in eight of 61 patients (13%)[16]. The drug was not known for each patient in our study and may differ between those receiving droperidol, midazolam or both.…”
Section: Discussionmentioning
confidence: 80%
“…Frequent dosing, with little or no short-lived effects, results in ongoing risks to staff and patient. Many modern substance abusers are naive to barbiturates, but may be highly tolerant of benzodiazepines [3]. When emergency physicians are selecting a sedative agent for an acutely agitated and violent patient they need to consider various factors including safety [4].…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, there are not published double-blind, randomized, placebo controlled trials comparing the efficacy and safety of benzodiazepines to neuroleptics or the combination of benzodiazepines and neuroleptics in 2C intoxication or excited delirium. Benzodiazepines can be used to treat agitation, hypertension, tachycardia, and hyperthermia [44,45]. Neuroleptics can be used in the setting of hallucinogeninduced agitation, although some controversy exists regarding their use.…”
Section: Treatmentmentioning
confidence: 99%